Application of Causal Inference to the Analysis of Occupant Thermal State and Energy Behavioral Intentions in Immersive Virtual Environments - Rentala, Girish; Zhu, Yimin; Mukhopadhyay, Supratik (Frontiers in Sustainable Cities, 2021)
Identification and quantitative understanding of factors that influence occupant energy behavior and thermal state during design phase is a critical aspect in supporting effective energy efficient design. To achieve this, immersive virtual environments (IVEs) have recently emerged as a potential tool to simulate occupant behaviors and collect context-dependent behavior data for buildings under design. On the other hand, the occupant energy behaviors and their influencing factors have been previously modelled using correlation-based approaches which fail to capture the underlying causal interactions. Therefore, in this study, the authors investigate the applicability of a causal inference framework to identify the causing factors that influence the occupant/participant energy behavioral intentions and their thermal states in IVE condition and compare those results with the baseline in-situ condition. A set of experiments involving 72 human subjects were conducted using a head mounted device (HMD) in a climate chamber. The subjects were exposed to three different step temperatures (cool, neutral, warm) under an IVE condition and a baseline in-situ condition. Participants individual factors, behavioral factors, skin temperatures, virtual experience factors, thermal states (sensation, acceptability, comfort) and energy behavioral intentions were collected during the experiments. Structural causal models were learnt from data using the elicitation method in conjunction with the PC-Stable algorithm. The findings show that the causal inference framework is a potentially effective method for identifying causing factors of thermal states and energy behavioral intentions as well as quantifying their causal effects. In addition, the study shows that the virtual experience factors are not causal factors of thermal states and energy behavioral intentions in IVE experiments. Furthermore, the study suggests that factors related to the theory of planned behavior is potentially a causal factor of energy behavior intentions; and the indoor temperature has a causal influence on general thermal sensation and overall skin temperature. Other findings including discrepancies, limitations of the study, and recommendations for future studies are also discussed.